Evaluating alternatives to flow cytometry for sex-sorting rhinoceros sperm - Louisa A. Rispoli; Elizabeth Donelan; Parker M. Pennington; Priscilla H. Joyner; Terri L. Roth (Theriogenology Wild)
Effective sperm sex-sorting techniques could be beneficial for managing ex-situ rhinoceros populations. Fluorescence-activated cell sorting (FACS) technology has shown promise but is limited by high cost, long sorting times, and poor compatibility with frozen sperm. This study evaluated two alternative methods for sex-sorting sperm from white (Ceratotherium simum; n = 5) and greater one-horned (Rhinoceros unicornis; n = 5) rhinoceroses. Thirteen ejaculates (five fresh and eight cryopreserved) were used to assess Toll-like receptor (TLR) activation and magnetic-activated cell sorting (MACS). The TLR method selectively reduces X-bearing sperm motility via a TLR agonist, whereas MACS separates sperm based on Y-bearing sperm having a more positive surface charge than X-bearing sperm. The TLRs were confirmed to be present in rhinoceros sperm, with TLR7 primarily localized to the head region (90–95 %) and TLR8 to the flagellum (∼50 %). Activation with a TLR8 ligand reduced velocity (P = 0.001) but did not alter the distribution of X- and Y-bearing sperm in the upper and lower swim-up layers (P = 0.259). Negatively charged magnetic nanoparticles associated and pulled a portion of sperm to the tube wall when magnetic force was applied, leaving 35–80 % of sperm free in suspension, depending on the treatment conditions. However, no enrichment for X-bearing sperm was observed in the unbound fraction (P > 0.27). These results indicate that neither method physically separated X- from Y-bearing rhinoceros sperm under the tested conditions. Nonetheless, the findings provide important foundational data for refining alternative methods for sex-sorting in this species and highlight both the potential and the challenges of applying such methods.